Autologous Fat Grafting for Scleroderma-Induced Digital Ulcers. An Effective Technique in Patients with Systemic Sclerosis - Bene, M. Del; Pozzi, M. R.; Rovati, L.; Mazzola, I.; Erba, G.; Bonomi, S. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2014)
Background: Digital ulcers (DUs) occur in up to 50% of patients with Systemic Sclerosis (SSc). DUs are painful, recurring and lead to functional disability. Management of DUs includes pharmacologic and local therapy, the healing process is slow and the ulcer can become infected or evolve to gangrene. Autologous fat grafting (AFG) is a technique used to promote tissues repair. We used AFG to treat DUs refractory to conventional treatment to enhance healing process.Patients and Methods: We treated 9 SSc patients for a total of 15 ulcers. All 9 patients were treated with iv Iloprost. The purified fat tissue was injected at the border of larger ulcers or at the finger base of smaller DUs. The AFG was performed from 2 to 8 months since the ulcer onset.Results: Complete healing occured in 10 DUs and size reduction ≥50% in 2, within 8–12 weeks. In all but 2 patients the pain improved allowing a reduction of analgesics. In the majority of the cases AFG was able to hasten ulcer healing and to reduce pain and the need of pharmacological therapy. The lack of efficacy on healing and pain reduction was observed when the ulcers were long-lasting, located on legs and with concurrent atherosclerotic macroangiopathy.Conclusions: Surgical resective treatment for finger ulcers in patients affected by SSc is fraught with morbidity and long prolonged recovery. This study introduces a novel minimally invasive approach. The procedure is safe and effective, with short recovery time and local deficient vascularization improvement.
Keywords: autologous fat grafting; digital ulcers; systemic sclerosis; chronic ischemia; adipose-derived stem cells